The portfolio balance channel of quantitative easing in a DSGE model with financial frictions - Genevieve Nelson (Danmarks Nationalbank, 2021)
Investors who arbitrage between long term government debt and corporate debt expand the Portfolio Balance Channel in that the effects of QE spill over to the overall cost of corporate borrowing. I find that overall the Federal Reserve's second round of Large-Scale Asset Purchases (LSAPII) boosts output between 0.5 - 1.7%, the equivalent of a 83 - 279 basis point cut in the Federal Funds rate. The long term maturity preference of investors increases output growth by between 0.4 and 1.3% points, and inflation between 20 and 68 annualized basis points more than the model without this expanded channel.
Keywords: E13; E52; 330; Monetary Policy; Monetary-policy instrument